Decrease of contact allergy to hydroxyisohexyl 3-cyclohexene carboxaldehyde in Europe prior to its ban and diagnostic value - Ahlström, Malin G.; Uter, Wolfgang; Ahlström, Magnus G.; Johansen, Jeanne D. (Contact Dermatitis, 2021)
Background: Hydroxyisohexyl 3-cyclohexene carboxaldehyde (HICC) has been the most reported fragrance chemical for two decades and will be prohibited in cosmetic products from August 2021. Objectives: To describe the time trend of HICC contact allergy in European patients with dermatitis in 2009 to 2019, and the added value of testing HICC separately in the baseline series. Methods: Data were reviewed for 124 472 patients with dermatitis who were patch tested with HICC 5% pet. in the baseline series in the European Surveillance System on Contact Allergy (ESSCA) network (2009 to 2018) and at the Herlev-Gentofte Hospital Department of Dermatology and Allergy (2009 to 2019). Results: Contact allergy to HICC was found in 1.98% of 9865 patients in Gentofte and 1.62% of 114 607 patients in the ESSCA network. Overall, the prevalence decreased annually, with 0.156 percentage points (P =.001) in Gentofte and 0.051 percentage points (P =.0002) in ESSCA. The frequency of missed contact allergy to HICC when testing only with fragrance mix II (FMII) was 0.17% (17/9865) and 0.35% (405/114607) of the whole test population in the Gentofte and ESSCA populations, respectively. Conclusions: This is the first study to demonstrate a significant decline in HICC allergy in European patients with dermatitis, most likely attributed to the upcoming European ban.
CRIS-Team Scopus Importer:2021-02-05
Keywords: clinical epidemiology; contact allergy; hydroxyisohexyl 3-cyclohexene carboxaldehyde; RRID:SCR_001905